Structural basis of the membrane intramolecular transacylase reaction responsible for lyso-form lipoprotein synthesis - Samir Olatunji (Nature Portfolio, 2021)
In Gram-positive bacteria, lipoprotein intramolecular transacylase Lit produces a lipoprotein variant with less immunogenicity. As such, Lit can be viewed as a virulence factor. Here, structural and functional characterization of the enzyme provides insight into its catalytic mechanism, setting the stage for future studies of Lit as a target for new antibiotics.